Love-Hate Relationship: Australia, Timor and a Rising China - Horta, Loro (2016)
Emerging security challenges in Asia are compelling the international community to take a hard look at their causes and implications on state and human security. Given the growing complexity of these challenges, responding to them require more innovative approaches.